CROP HOST SPECIFICITY OF CROP HOST SPECIFICITY OF XANTHOMONAS CAMPESTRIS AMPESTRIS AMPESTRIS PV. VESICATORIA PREVALENT IN NASHIK DISTRICT IN INDIA - T. S. AJAYASREE; S. G. BORKAR (The Bioscan, 2018)
The bacterial leaf spot and blight disease pathogen of tomato prevalent extensively in tomato growing areas of Nashik district causes up to 40 percent yield losses. The bacterial pathogen was isolated from infected tomato leaves sample, purified and identified as Xanthomonas campestris pv. vesicatoria based on various morphological ,biochemical and host specificity test. The isolated bacterial colonies were yellow, raised, round and translucent. The bacterium was gram negative with single polar flagellation. The bacterium was oxidative, did not produce the fluorescent pigment, did not reduce the nitrate and did not produce oxidase. It induced the HR on tobacco. The bacterium was positive for hydrolysis of esculin, gelatinase activity, H2S production, Tween esterase activity and amidan. Similarly the bacterium was able to utilize the sugar arabinose, glucose, galactose and cellobiose. This bacterial pathogen was specific for the infection to the tomato crop plant and does not infect its other natural host chilli and capsicum. The significance of this study is that the bacterial pathogen X.c.pv.vesicatoria prevalent in Nashik district on tomato crop is not a threat to chilli and capsicum crops grown in the region as the strain is host specific.